Genome‐wide linkage analysis of pulmonary function in families of children with asthma in Costa Rica - Hersh, Craig P (BMJ Group, 2007)
BACKGROUND: Although asthma is highly prevalent among certain Hispanic subgroups, genetic determinants of asthma and asthma‐related traits have not been conclusively identified in Hispanic populations. A study was undertaken to identify genomic regions containing susceptibility loci for pulmonary function and bronchodilator responsiveness (BDR) in Costa Ricans. METHODS: Eight extended pedigrees were ascertained through schoolchildren with asthma in the Central Valley of Costa Rica. Short tandem repeat (STR) markers were genotyped throughout the genome at an average spacing of 8.2 cM. Multipoint variance component linkage analyses of forced expiratory volume in 1 second (FEV(1)) and FEV(1)/ forced vital capacity (FVC; both pre‐bronchodilator and post‐bronchodilator) and BDR were performed in these eight families (pre‐bronchodilator spirometry, n = 640; post‐bronchodilator spirometry and BDR, n = 624). Nine additional STR markers were genotyped on chromosome 7. Secondary analyses were repeated after stratification by cigarette smoking. RESULTS: Among all subjects, the highest logarithm of the odds of linkage (LOD) score for FEV(1) (post‐bronchodilator) was found on chromosome 7q34–35 (LOD = 2.45, including the additional markers). The highest LOD scores for FEV(1)/FVC (pre‐bronchodilator) and BDR were found on chromosomes 2q (LOD = 1.53) and 9p (LOD = 1.53), respectively. Among former and current smokers there was near‐significant evidence of linkage to FEV(1)/FVC (post‐bronchodilator) on chromosome 5p (LOD = 3.27) and suggestive evidence of linkage to FEV(1) on chromosomes 3q (pre‐bronchodilator, LOD = 2.74) and 4q (post‐bronchodilator, LOD = 2.66). CONCLUSIONS: In eight families of children with asthma in Costa Rica, there is suggestive evidence of linkage to FEV(1) on chromosome 7q34–35. In these families, FEV(1)/FVC may be influenced by an interaction between cigarette smoking and a locus (loci) on chromosome 5p.